Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Perinatal exposure to environmental chemicals that disrupt thyroid function can perturb testis development - Monica K. Draskau; Ida W. Strand; Raul Ayala Davila; Anne-Sofie R. Ballegaard; Mikael Pedersen; Louise Ramhøj; Sofie Rising; Kieu-mi Tran; Marta Axelstad; Josephine Bowles; Anna K. Rosenmai; Cassy M. Spiller; et al. (Environmental Pollution, 2024)

An aphid symbiont confers protection against a specialized RNA virus, another increases vulnerability to the same pathogen - Clesson H. V. Higashi; William L. Nichols; Germain Chevignon; Vilas Patel; Suzanne E. Allison; Kyungsun Lee Kim; Michael R. Strand; Kerry M. Oliver (Molecular Ecology, 2023)
Insects often harbour heritable symbionts that provide defence against specialized natural enemies, yet little is known about symbiont protection when hosts face simultaneous threats. In pea aphids ( Acyrthosiphon pisum ), the facultative endosymbiont Hamiltonella defensa confers protection against the parasitoid, Aphidius ervi , and Regiella insecticola protects against aphid‐specific fungal pathogens, including Pandora neoaphidis . Here, we investigated whether these two common aphid symbionts protect against a specialized virus A . pisum virus (APV), and whether their antifungal and antiparasitoid services are impacted by APV infection. We found that APV imposed large fitness costs on symbiont‐free aphids and these costs were elevated in aphids also housing H . defensa . In contrast, APV titres were significantly reduced and costs to APV infection were largely eliminated in aphids with R . insecticola . To our knowledge, R . insecticola is the first aphid symbiont shown to protect against a viral pathogen, and only the second arthropod symbiont reported to do so. In contrast, APV infection did not impact the protective services of either R . insecticola or H . defensa . To better understand APV biology, we produced five genomes and examined transmission routes. We found that moderate rates of vertical transmission, combined with horizontal transfer through food plants, were the major route of APV spread, although lateral transfer by parasitoids also occurred. Transmission was unaffected by facultative symbionts. In summary, the presence and species identity of facultative symbionts resulted in highly divergent outcomes for aphids infected with APV, while not impacting defensive services that target other enemies. These findings add to the diverse phenotypes conferred by aphid symbionts, and to the growing body of work highlighting extensive variation in symbiont‐mediated interactions.

Cardiomyocyte-specific overexpression of syndecan-4 in mice results in activation of calcineurin-NFAT signalling and exacerbated cardiac hypertrophy - Ida G. Lunde; J. Magnus Aronsen; A. Olav Melleby; Mari E. Strand; Jonas Skogestad; Bård A. Bendiksen; M. Shakil Ahmed; Ivar Sjaastad; Håvard Attramadal; Cathrine R. Carlson; Geir Christensen (Molecular Biology Reports, 2022)
Background Cardiomyocyte hypertrophy is a hallmark of cardiac dysfunction in patients with aortic stenosis (AS), and can be triggered by left ventricular (LV) pressure overload in mice by aortic banding (AB). Syndecan-4 is a transmembrane heparan sulphate proteoglycan which is found increased in the myocardium of AS patients and AB mice. The role of syndecan-4 in cardiomyocyte hypertrophy is not well understood. Purpose of the study We developed mice with cardiomyocyte-specific overexpression of syndecan-4 ( Sdc4-Tg ) and subjected these to AB to examine the role of syndecan-4 in hypertrophy and activation of the pro-hypertrophic calcineurin-NFAT signalling pathway. Methods and results Sdc4-Tg mice showed exacerbated cardiac remodelling upon AB compared to wild type (WT). At 2–6 weeks post-AB, Sdc4-Tg and WT mice showed similar hypertrophic growth, while at 20 weeks post-AB, exacerbated hypertrophy and dysfunction were evident in Sdc4-Tg mice. After cross-breeding of Sdc4-Tg mice with NFAT-luciferase reporter mice, we found increased NFAT activation in Sdc4-Tg hearts after AB. Immunoprecipitation showed that calcineurin bound to syndecan-4 in Sdc4-Tg hearts. Isolated cardiomyocytes from Sdc4-Tg mice showed alterations in Ca 2+ fluxes, suggesting that syndecan-4 regulated Ca 2+ levels, and thereby, activating the syndecan-4-calcineurin complex resulting in NFAT activation and hypertrophic growth. Similarly, primary cardiomyocyte cultures from neonatal rats showed increased calcineurin-NFAT-dependent hypertrophic growth upon viral Sdc4 overexpression. Conclusion Our study of mice with cardiomyocyte-specific overexpression of Sdc4 have revealed that syndecan-4 is important for activation of the Ca 2+ -dependent calcineurin-NFAT signalling pathway, hypertrophic remodelling and dysfunction in cardiomyocytes in response to pressure overload.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

A first report on coexistence and hybridization of Mytilus trossulus and M. edulis mussels in Greenland - R. Wenne; L. Bach; M. Zbawicka; J. Strand; J. H. McDonald (Polar Biology, 2016)

Long‐term dynamics of mycorrhizal root tips in a loblolly pine forest grown with free‐air CO 2 enrichment and soil N fertilization for 6 years - Seth G. Pritchard; Benton N. Taylor; Emily R. Cooper; Katilyn V. Beidler; Allan E. Strand; M. Luke McCormack; Siyao Zhang (Global Change Biology, 2014)
Large‐scale, long‐term FACE (Free‐Air CO 2 enrichment) experiments indicate that increases in atmospheric CO 2 concentrations will influence forest C cycling in unpredictable ways. It has been recently suggested that responses of mycorrhizal fungi could determine whether forest net primary productivity ( NPP ) is increased by elevated CO 2 over long time periods and if forests soils will function as sources or sinks of C in the future. We studied the dynamic responses of ectomycorrhizae to N fertilization and atmospheric CO 2 enrichment at the Duke FACE experiment using minirhizotrons over a 6 year period (2005–2010). Stimulation of mycorrhizal production by elevated CO 2 was observed during only 1 (2007) of 6 years. This increased the standing crop of mycorrhizal tips during 2007 and 2008; during 2008, significantly higher mortality returned standing crop to ambient levels for the remainder of the experiment. It is therefore unlikely that increased production of mycorrhizal tips can explain the lack of progressive nitrogen limitations and associated increases in N uptake observed in CO 2 ‐enriched plots at this site. Fertilization generally decreased tree reliance on mycorrhizae as tip production declined with the addition of nitrogen as has been shown in many other studies. Annual NPP of mycorrhizal tips was greatest during years with warm January temperatures and during years with cool spring temperatures. A 2 °C increase in average late spring temperatures (May and June) decreased annual production of mycorrhizal root tip length by 50%. This has important implications for ecosystem function in a warmer world in addition to potential for forest soils to sequester atmospheric C.

Mycorrhizal and rhizomorph dynamics in a loblolly pine forest during 5 years of free‐air‐CO 2 ‐enrichment - S. G. PRITCHARD; A. E. STRAND; M. L. McCORMACK; M. A. DAVIS; R. OREN (Global Change Biology, 2008)
Soil fungi couple plant and ecosystem resource demands to pools of soil resources. Research on these organisms is needed to predict how rising atmospheric CO 2 will influence forest ecosystem processes and soil carbon (C) sequestration potential. We examined the influence of free‐air‐CO 2 ‐enrichment (FACE) on mycorrhizal and extraradical rhizomorph dynamics over a 5‐year period in a loblolly pine forest using minirhizotrons. Standing crop of mycorrhizal root tips varied greatly spatially and through time. Summed across all years, CO 2 enrichment increased mycorrhizal root tip production by 194% in deep soil (15–30 cm) but did not influence mycorrhizal production in shallow soil (0–15 cm). Production and mortality of soil rhizomorph length was 27% and 25% greater in CO 2 ‐enriched plots compared with controls over a 5‐year period beginning in January of 2000 and running through autumn 2004. Effects of atmospheric CO 2 enrichment on longevity of mycorrhizal root tips and rhizomorphs varied with soil depth (mycorrhizae and rhizomorphs) and with diameter (rhizomorphs). For instance, survival of mycorrhizal tips was reduced in CO 2 ‐enriched plots in deep soil (15–30 cm depth) but was increased in shallower soil (0–15 cm). Rhizomorph turnover was accelerated in shallow soil but effects on survivorship in deep soil varied according to diameter. A drought in 2002 coupled with loss of leaf area to an ice storm late in 2002 were followed by reductions in rhizomorph and mycorrhizal production, increases in mortality, and decreases in standing crop during 2003 and 2004. These effects tended to be more severe in CO 2 ‐enriched plots. Positive effects of atmospheric CO 2 enrichment on mycorrhizal fungi, primarily observed in deeper soil, are probably contributing to the prolonged stimulation of NPP by CO 2 enrichment at the Duke FACE study site.

Parallel climate model (PCM) control and transient simulations - W. M. Washington; J. W. Weatherly; G. A. Meehl; A. J. Semtner Jr.; T. W. Bettge; A. P. Craig; W. G. Strand Jr.; J. Arblaster; V. B. Wayland; R. James; Y. Zhang (Climate Dynamics, 2000)

Superparasitism and ovicide in parasitic Hymenoptera: theory and a case study of the ectoparasitoid Bracon hebetor - M. R. Strand; H. C. J. Godfray (Behavioral Ecology and Sociobiology, 1989)

Stimulation of oviposition and successful rearing ofTelenomus heliothidis [Hym.: Scelionidae] on nonhosts by use of a host-recognition kairomone - M. R. Strand; S. B. Vinson (BioControl, 1982)